(untitled) (International Journal of Biomedical and Advance Research, 2015)
Background: The addictive liability and pharmacological effects of smoking are primarily mediated by the major tobacco alkaloid nicotine. Cigarette smoke may promote atherogenesis by producing oxygen-derived free radicals that damage lipids. Cigarette smoking is associated with impaired endothelium-dependent vasodilatation and cardiovascular disease (CVD). Aim: The Aim of our study was to determine the Level of lipid profile, liver function, crp and MDA in Cigarette Smokers. Method: A Total No. of 100 subjects were selected ,out of which 50 were healthy individual and 50 were Chronic Smokers .The lipid parameter and Liver function were estimated by enzymatic method, CRP were estimated by Turbidometric kit method and MDA level were estimated by thiobarbituric Acid (TBA) method. Result: Smokers have a significant higher level of liver enzyme (AST, ALT, ALP), lipid parameter (CHO,TG,LDL), MDA and CRP and decreased significant level of HDL and serum protein.